Childhood nephrotic syndrome in Southeast Nigeria: The old story or any change in pattern? - Okoronkwo, Nneka Chioma; Onyearugha, Chukwuemeka Ngozi (Indian Journal of Child Health, 2020)
Background: The chronic course of nephrotic syndrome (NS), it is racial/regional variations, and associated risk of end-stage renal disease is of great pediatric importance. This underscores the need to study the characteristics of this cohort of patients in every nephrology setting. Objective: This study was aimed at documenting the characteristics of children presenting with NS in our hospital. Materials and Methods: This was a cross-sectional descriptive study of children aged 29 days–16 years admitted and managed for NS over 5 years at the Pediatric Nephrology Unit of the Abia State University Teaching Hospital, Nigeria. Children diagnosed with NS in our setting were consecutively enrolled in the study. The parameters documented and analyzed for each patient with NS included Biodata, presenting complaints, duration of illness before the presentation, intake of herbal concoctions, results of investigations done, response to the steroids, duration of treatment before remission, and outcome of admission. Steroid sensitive NS was followed up for a median (range) period of 18.2 (12.0–24.0) months to monitor remission and relapse. Results: A total of 6108 children were admitted into the pediatric wards during the study period, of which 104 were renal disorders. NS accounted for 0.8% of all the pediatric admissions and 49 (47.1%) of the admitted renal disorders. Male:female ratio was 2.3:1. The mean age was 8.35±3.99 years, with peak ages between 7 and 9 years. The major clinical features at first presentation were pedal edema (93.9%) and oliguria (87.8%). A total of 19 patients (38.9%) took herbal concoctions before the presentation (p<0.05) and 12 patients had culture-proven urinary tract infections. There were four patients seropositive to human immunodeficiency virus and two had sickle cell anemia. There were 39 patients (90.7%) who were steroid-sensitive, while four (9.3%) were steroid-resistant. A total of 47 patients were discharged. There was one patient who was referred, while one signed against medical advice. Over this period, 76.9% remained in remission, while relapse was noted in 23.1% of patients. The mortality was 2.0%. Conclusion: NS forms a significant part of our pediatric admissions. Herbal concoction intake among our cohort with NS was high. There was an increased response to the steroid, even in older children. A majority maintained their remission while on follow-up. The mortality rate was low. The prognosis of NS in African children is changing for the better, age notwithstanding.